The Development of Digital Storytelling in German Lessons - Hafniati Hafniati; Ahmad Bengar Harahap; Sapitri Sapitri (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
This study aims to develop a digital storytelling in German lessons. The process of digital storytelling in German lessons consists of the explanations of the phases of Richey and Klein theory. These include: (1) planning, (2) creation, (3) evaluation. The data of this research are images, sounds, videos, text material about “City of Medan”. The data sources in this research are based on the book “Potensi Objek dan Daya Tarik Wisata Budaya Dalam Pengembangan Pariwissata di Kota Medan” and website of “Pemko Medan”. This research is carried out in the German department of the Faculty of Language and Arts at the State University of Medan. The result of this creation research is a video digital storytelling about "City of Medan". The creation of the digital storytelling will be evaluated by the experts. The results of the evaluation show that digital storytelling is very good. This is how the video Digital Storytelling can be used in German lessons.